Accounting Information Systems on The Financial Performance of Batik MSMEs in Solo Raya through The Quality of Financial Reports: The Role of Accounting Understanding as Moderation - Sarsiti, Sarsiti (Green Publisher Indonesia, 2020)
The research objectives are to analyze the influence of accounting information systems (AIS) on the quality of financial reports, the influence of accounting information systems and financial report quality on financial performance, analyze the influence of accounting information systems on the quality of financial reports moderated by accounting understanding, and analyze the indirect influence of accounting information systems on financial performance through quality of financial reports. The sample is 77 batik SMEs in the Greater Solo area. Data analysis uses SEM-PLS where data processing uses Smart-PLS version 3. The results of this research show that (1) the accounting information system has a significant effect on the quality of financial reports (2) the accounting information system does not have a significant effect on the financial performance of MSMEs (3) the quality of financial reports has a significant effect on the financial performance of MSMEs (4) understanding of accounting cannot moderate the influence of accounting information systems on the quality of financial reports (5) accounting information systems have an indirect effect on the financial performance of MSMEs through the quality of financial reports.